Learning from your mistakes: does it matter if you're out in left foot, I mean field?. Issue 9 (21st October 2018) - Cyr, Andrée-Ann; Anderson, Nicole D.
ABSTRACT: Studies have shown that generating errors prior to studying information ( pencil –?) can improve target retention relative to passive (i.e., errorless) study, provided that cues and targets are semantically related ( pencil – ink ) and not unrelated ( pencil-frog ). In two experiments, we manipulated semantic proximity of errors to targets during trial-and-error to examine whether it would modulate this error generation benefit. In Experiment 1, participants were shown a cue ( band – ? ) and asked to generate a related word (e.g., drum ). Critically, they were given a target that either matched the semantic meaning of their guess ( guitar ) or mismatched it ( rubber ). In Experiment 2, participants studied Spanish words where the English translation either matched their expectations ( pariente – relative ) or mismatched it ( carpeta – folder ). Both experiments show that errors benefit memory to the extent that they overlap semantically with targets. Results are discussed in terms of the retrieval benefits of activating related concepts during learning.